2016
DOI: 10.1021/acs.jnatprod.6b00508
|View full text |Cite
|
Sign up to set email alerts
|

Rearranged 6/6/5/6-Fused Triterpenoid Acids from the Stems of Kadsura coccinea

Abstract: Fourteen new rearranged 6/6/5/6-fused triterpenoid acids, namely, kadcoccine acids A-N (1-14), were isolated from an EtOAc-soluble extract of the stems of Kadsura coccinea. Their structures were characterized mainly by analyzing 1D and 2D NMR and HRESIMS data and were shown to feature a rare 14(13→12)-abeo-lanostane skeleton. Compounds 7 and 8 represented the first examples of a 5-substituted 2(5H)-furanone motif on the C-17 side chain of this skeleton. The absolute configurations of C-23 for compounds 1, 7, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The 13 C NMR and DEPT spectra ( Table 2 ) of 1 showed thirty carbon resonances ascribed to seven methyls, six methylenes, six methines (one aromatic/olefinic carbon), eleven quaternary carbons (three ketone groups, one carboxyl group, three aromatic/olefinic carbons, one oxygenated carbon and three aliphatic carbons). These data suggested that 1 was a lanostane-type triterpenoid, which was the same as kadcoccine acid A 12 possessing a 14(13→12)- abeo -6/6/5/6-fused rearranged skeleton.…”
Section: Resultsmentioning
confidence: 87%
“…The 13 C NMR and DEPT spectra ( Table 2 ) of 1 showed thirty carbon resonances ascribed to seven methyls, six methylenes, six methines (one aromatic/olefinic carbon), eleven quaternary carbons (three ketone groups, one carboxyl group, three aromatic/olefinic carbons, one oxygenated carbon and three aliphatic carbons). These data suggested that 1 was a lanostane-type triterpenoid, which was the same as kadcoccine acid A 12 possessing a 14(13→12)- abeo -6/6/5/6-fused rearranged skeleton.…”
Section: Resultsmentioning
confidence: 87%
“…Detailed analysis of the 1D and 2D NMR spectra of 1 demonstrated its structure to be similar to those of kadcoccine acids A–N [ 8 ], which had 14(13 → 12)-abeolanostane scaffolds featuring 6/6/5/6-fused ring systems. The planar structure of 1 could be confirmed by its 1 H- 1 H COSY and HMBC data (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of single Xenopus embryo cells with kadsuracoccinic acid A is reported to be capable of detained cleavage of these cells with an IC50 value of 0.32 μg/ml (H. Li, Wang, Miyata, & Kitanaka, 2008). Hu et al (2016) tested six human cancer cell lines including HL‐60, SMMC‐7721, A‐549, MCF‐7, SW‐480 and HeLa cells with kadcoccine acids A‐N. Only kadcoccine acids B and H, showed activity with IC50 values varying from 3.11 to 7.77 μmol/L.…”
Section: Discussionmentioning
confidence: 99%